Optimalisasi Pra Literasi Anak Usia Dini Melalui Pendampingan Baca-Tulis Berbasis Bahasa Ibu - Fono, Yasinta Maria; Ita, Efrida; Pango, Kristalana; Eno, Prudensia (Civiliza Publishing, 2024)
The aim of this community service program was to optimize early literacy skills in young children through a mother tongue-based reading and writing assistance. The program was conducted over six months, involving children aged 4-6 years in Kober Peupado Malanuza village. The assistance focused on letter recognition, simple words, and interactive activities involving parents in supporting children’s learning at home. The results of the program implementation showed significant progress in children’s ability to recognize letters and words, as well as an increased interest in reading and writing activities. The mother tongue-based teaching method proved effective, as children found it easier to understand and remember vocabulary and language structures they used in daily life. Parental involvement also played a crucial role in reinforcing the learning process. However, some challenges related to limited resources and infrastructure at the location need to be addressed to improve the quality of the program. Based on these findings, it is recommended to continue the program by expanding access to learning materials, strengthening training for parents and teachers, and introducing a community-based approach for program sustainability. Overall, optimizing early literacy skills through a mother tongue-based approach shows significant positive impacts in supporting a more comprehensive and meaningful literacy development for children.